Historical Roots of Scientific Museums (18th–19th Centuries) (Uzbekistan Open Conference, 2025)
This scientific article examines the formation of scientific museums during the 18th–19th centuries, their role in socio-cultural development, and the influence of the Enlightenment, scientific societies, and expeditions on the development of museology. The study employs historical sources and comparative analysis methods. The findings indicate that the emergence of scientific museums was driven by the growing importance of science in society, the need to preserve scientific heritage, and the development of the education system.